Clinical utility and impact of autopsies on clinical practice among doctors in a large teaching hospital in Ghana - Edem Tette; Alfred E. Yawson; Yao Tettey (Taylor & Francis Group, 2014)
Background : Autopsies can provide a good indication of the quality of patient care, in terms of the accuracy of clinical diagnosis and the quality of treatment given. Designs : This was a cross-sectional study among clinicians at the Korle-Bu Teaching Hospital (KBTH) in 2012. Data were collected with a 69-item, self-administered, structured questionnaire. A total of 215 questionnaires were sent out and 119 clinicians responded. Data were collected on the benefits and utility of autopsies for medical practice, care of patients, and management of clinical wards. Survey data were analyzed by simple descriptive statistics (i.e. proportions, ratios, and percentages). Data were analyzed using SPSS version 21. Objective : This study examined the views of clinicians regarding the utility of autopsies and their influence on clinical practice in a large teaching hospital in Ghana. Results : Overall, clinicians in KBTH agreed that autopsy reports are useful in answering clinical questions (55/119; 46.2%), confirming or verifying clinical diagnoses (54/119; 45.4%), providing information on unsuspected diagnoses (40/119; 33.6%), and for medical education (90/119; 75.6%). Overall, 70/119 (58.8%) of clinicians agreed that autopsy findings improve completeness and reliability of death certification and provide information on clinical effectiveness of treatment and patient management. However, only 23/119 (19.3%) of sampled clinicians had personal interactions with a pathologist during autopsy processes and 93/119 (78.2%) had not attended any autopsy demonstrations in the past 6 months. Attendance of pathologists at clinicopathological meetings of clinical departments of KBTH was minimal. Unfortunately, the use of autopsy reports for auditing clinical diagnostic performance was not seen as essential. Conclusion : Strengthening the interaction between doctors and pathologists is essential in improving the autopsy process and utilization in the hospital. KBTH should create opportunities for doctors to attend autopsy demonstrations and for pathologists to attend clinicopathological meetings in the hospital.